High-quality LED epitaxial structure and preparation method thereof

By using the alternating cyclic layer of high-temperature pause layer/low-temperature buffer layer in the GaN epitaxial layer as the nucleation layer, and adding high-voltage and AL doping in the roughening layer stage, combined with the 2D/3D hybrid growth mode of the recovery layer, the problem of low quality of the GaN epitaxial layer in the prior art is solved, and a high-quality LED epitaxial structure and improved luminous efficiency are achieved.

CN119816016AActive Publication Date: 2025-04-11JUCAN PHOTOELECTRIC TECH (SUQIAN) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411794513.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-11
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

In the prior art, the mass of the GaN epitaxial layer is caused by the problems of excessive nucleation grain density, low grain quality, high probability of impurities overflow, and unhealing of dislocations at the end of healing, resulting in low crystal quality.

Method used

The alternating cycle layer of high-temperature pause layer/low-temperature buffer layer is used as the nucleation layer, and high-voltage and AL doping are added in the coarse layer stage to reduce the nucleus density and dislocation density through the 3D growth mode, and the 2D/3D hybrid growth mode of the recovery layer is combined to improve the grain healing quality.

Benefits of technology

Low-density and high-quality crystal nuclei formation are achieved, the dislocation density at the grain boundary is reduced, the overall quality of the crystal is improved, and the luminous efficiency of the LED epitaxial structure is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816016A_ABST
    Figure CN119816016A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of light emitting diodes, in particular to a high-quality LED epitaxial structure and a preparation method thereof, through the design of a novel nucleating layer, low-density and high-quality crystal nucleuses can be formed, the density of crystal grains formed on a subsequent high-pressure coarsening layer is lower, and the size of the crystal grains is larger. And the healing time between subsequent crystal grains is prolonged, and the dislocation density at the crystal grain healing boundary is reduced. AL is doped in the initial stage of 3D oscillation starting, GaN growth on the non-C surface of the PSS can be inhibited to a certain extent, and the lattice quality is improved; in the nucleation layer and coarsening layer stages, a 3D growth mode is inclined, the V / III ratio is reduced, the pressure is improved, crystal nucleus and crystal grain growth is facilitated, the crystal nucleus density is reduced, and the dislocation density at the surface healing position can be reduced. In the growth stage of the recovery layer, a 2D / 3D mixed growth mode is inclined, the temperature is raised, the V / III ratio is increased, and the pressure is reduced, so that the healing of crystal grains is facilitated, and the transverse growth speed is higher than the vertical growth speed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of light emitting diodes, and in particular relates to a high-quality LED epitaxial structure and a preparation method thereof. Background Art

[0002] The direct growth of GaN on sapphire substrates has long been hindered by the limitations of too high dislocation density, too high n-type background concentration and difficulty in achieving P-type doping. Some people have proposed and studied that low-temperature GaN buffer layers can more effectively improve the quality of GaN epitaxial layers. Although many researchers have conducted extensive research on the growth conditions of the buffer layer and the use of the buffer layer growth process has greatly improved the quality of GaN, the following problems still exist: 1. The existing buffer layer structure has too high a nucleation grain density and low grain quality, which results in a high dislocation density at the grain boundary during healing, resulting in low final crystal quality. 2. In the early stage of crystal nucleus healing, the growth rate is too fast, which reduces the probability of C and other impurities overflowing due to the decomposition of metal organic matter during the growth process. These impurities will be incorporated into the epitaxial layer to become point defects. At the same time, the threading dislocations in the late stage of healing cannot heal in time and continue to grow upward, which eventually leads to the decline of crystal quality.

[0003] With the development of the industry and application needs, higher quality and more efficient epitaxial layer growth is imperative. Summary of the invention

[0004] In view of the problems in the background technology, the present invention develops a high-quality LED epitaxial structure and a preparation method thereof which further improves the quality of a buffer layer and a nucleation layer.

[0005] To achieve the above object, the present invention adopts the following technical solution: A high-quality LED epitaxial structure includes, from bottom to top, a substrate, a nucleation layer, a roughening layer, a recovery layer, an unintentional doping layer, an N-type GaN layer, a quantum well light-emitting layer, and a P-type GaN layer. The nucleation layer is an alternating cycle layer of a high-temperature pause layer / a low-temperature buffer layer, and the roughening layer includes a high-pressure roughening layer and an Al-doped roughening layer.

[0006] Furthermore, the substrate is a sapphire substrate.

[0007] Furthermore, a P-type electron blocking layer is provided between the quantum well light-emitting layer and the P-type GaN layer.

[0008] Furthermore, the low-temperature buffer layer is a non-doped GaN layer, and the high-temperature pause layer is a non-actual growth layer.

[0009] Furthermore, the high-pressure roughening layer is a non-actual production layer, and the Al-doped roughening layer is a low-pressure Al-doped GaN layer.

[0010] Furthermore, the recovery layer is a non-doped GaN layer.

[0011] Furthermore, the recovery layer includes recovery layer 1, recovery layer 2 and recovery layer 3, and the thickness is: recovery layer 2 < recovery layer 1 < recovery layer 3.

[0012] A method for preparing a high-quality LED epitaxial structure comprises the following steps: S01: Provide a substrate; S02: Depositing a novel nucleation layer on a substrate: The novel nucleation layer structure comprises: a low temperature slow The punch layer is a non-doped GaN layer: the thickness of a single cycle growth is 20A~25A, the growth atmosphere is N2, set to 200~400sccm, and the low temperature is set at 800~850℃; the high temperature pause layer is a non-actual growth layer: the high temperature is set at 880~950℃; the growth atmosphere is N2 and H2: N2 is set to 200~400sccm, and H2 is set to 200~400sccm; the number of high and low temperature cycles is set to 5~15 times; S03: depositing a novel roughening layer on the novel nucleation layer: the novel roughening layer structure comprises: a high-pressure roughening layer: a non-actual production layer, a high pressure setting of 300-400 torr, a growth atmosphere of N2, H2, NH3: N2 is set at 150-300 sccm, H2 is set at 100-200 sccm, and NH3 is set at 0-20 sccm; an AL-doped roughening layer: a low-pressure AL-doped GaN layer, a thickness of 300-500 nm, an AL amount of 5-20 slm, a low pressure setting of 150-250 torr, and a growth atmosphere of N2, H2, NH3: N2 is set at 150-300 sccm, H2 is set at 100-200 sccm, and NH3 is set at 150-300 sccm; S04: depositing a recovery layer on the novel roughening layer: the total thickness is 1500-2100 nm, which is a non-doped GaN layer, and the growth atmosphere is the same as the Al-doped roughening layer; the recovery layer structure comprises: Recovery layer 1, recovery layer 2, recovery layer 3; thickness: recovery layer 2 < recovery layer 1 < recovery layer 3; temperature: recovery layer 1 < recovery layer 2 < recovery layer 3; growth rate: recovery layer 1 < recovery layer 2 < recovery layer 3; S05: depositing an unintentionally doped GaN layer on the recovery layer; S06: depositing a Si-doped N_GaN layer on the unintentionally doped GaN layer; S07: depositing an MQW layer on the N_GaN layer; S08: depositing an AL-doped P_GaN EBL layer on the MQW layer; S09: depositing a high Mg-doped P_GaN layer on the Al-doped P_GaN EBL layer.

[0013] Furthermore, in step S04, the recovery layer 1 has a thickness of 300-500 nm, a temperature of 1030-1060° C., and a growth rate of 4.5-6 μm / h; Recovery layer 2: thickness 100~300nm, temperature 1070~1085℃, growth rate 6~7.5μm / h; Recovery layer 3: thickness is 1000-1300nm, temperature is 1090~1100℃, growth rate is 8~9μm / h.

[0014] Compared with the prior art, the present invention has the following beneficial effects: The LED epitaxial structure provided by the present invention includes a new nucleation layer and a new coarsening layer. Through the design of the new nucleation layer, a low-density, high-quality crystal nucleus can be formed. The density of the grains formed in the subsequent high-pressure coarsening layer will be lower, and the size of the grains will be relatively large. The time for subsequent healing between grains will be longer, and the dislocation density at the grain healing boundary will be reduced. The addition of Al in the initial stage of 3D oscillation can inhibit the growth of GaN on the non-C surface of PSS to a certain extent and improve the lattice quality; in the nucleation layer and coarsening layer stages, it tends to be a 3D growth mode, reducing the V / III ratio and increasing the pressure, which is conducive to the growth of crystal nuclei and grains, reducing the density of crystal nuclei, and reducing the dislocation density at the healing point of the interface. In the recovery layer growth stage, it tends to be a 2D / 3D mixed growth mode. Increasing the temperature, increasing the V / III ratio, and reducing the pressure are conducive to the healing of the grains, making the lateral growth rate greater than the vertical growth rate. The quality of the underlying lattice has been improved, laying a solid foundation for the subsequent growth of the N-type GaN layer, while also enlarging the growth window of the subsequent V Pits growth layer, thereby increasing the recombination probability of electrons and holes and improving the luminous efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is an LED epitaxial structure in the prior art.

[0016] Figure 2 This is the LED epitaxial structure of the present invention.

[0017] Figure 3 This is a comparison chart of the experiment of the present invention. DETAILED DESCRIPTION

[0018] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation mode, structure, characteristics and effects of the present invention are described in detail below in combination with the accompanying drawings and preferred embodiments.

[0019] like Figure 1As shown, the existing LED epitaxial structure includes, from bottom to top, a substrate, a buffer layer, a GaN layer, an N-type GaN layer, a quantum well light-emitting layer, a P-type electron blocking layer, and a P-type GaN.

[0020] like Figure 2 As shown, a high-quality LED epitaxial structure of the present invention includes, from bottom to top, a substrate, a novel nucleation layer, a novel roughening layer, a recovery layer, a GaN layer, an N-type GaN layer, a quantum well light-emitting layer, a P-type electron blocking layer, and a P-type GaN layer. The novel nucleation layer is an alternating cycle layer of a high-temperature pause layer / a low-temperature buffer layer, and the novel roughening layer includes a high-pressure roughening layer and an Al-doped roughening layer in sequence. The recovery layer includes recovery layer 1, recovery layer 2, and recovery layer 3, and the thickness is: recovery layer 2 < recovery layer 1 < recovery layer 3.

[0021] A method for preparing a high-quality LED epitaxial structure comprises the following steps: S01: Provide a substrate.

[0022] S02: Depositing a novel nucleation layer on a substrate: the novel nucleation layer structure comprises: Low temperature buffer layer, non-doped GaN layer: single cycle growth thickness 20~25A, growth The atmosphere is N2, set at 200~400sccm, and the low temperature is set at 800~850℃; The high-temperature pause layer is not an actual growth layer: the high temperature is set at 880~950℃; the growth atmosphere is N2 and H2: N2 is set at 200~400sccm, and H2 is set at 200~400sccm. High-temperature baking allows the nucleation layer to recrystallize; the number of high and low temperature cycles is set at 5~15 times, and repeated crystallization of the buffer layer is achieved through multiple high and low temperature cycle settings.

[0023] S03: depositing a novel roughening layer on the novel nucleation layer: the novel roughening layer structure comprises: High-pressure coarsening layer: It is not an actual production layer. It is high pressure in the initial stage. The high pressure is set to 300~400torr. The growth atmosphere is N2, H2, and NH3: N2 is set to 150~300sccm, H2 is set to 100~200sccm, and NH3 is set to 0~20sccm. The high pressure setting can reduce the molecular free path, reduce the density of grain islands in the coarsening layer, and increase the size of grain islands. Large and sparse islands can prolong the healing time of the recovery layer film and reduce edge dislocations at the grain boundaries. Al-doped coarsening layer: It is a low-pressure Al-doped GaN layer, an actual production layer, in the initial stage of recovery layer oscillation, with a thickness of 300~500nm, an Al amount of 5~20slm, a low pressure setting of 150~250torr, and a growth atmosphere of N2, H2, and NH3: N2 is set at 150~300sccm, H2 is set at 100~200sccm, and NH3 is set at 150~300sccm; Al doping can inhibit GaN growth on the non-C surface of the PSS substrate to a certain extent, reduce the initial dislocation, and improve the lattice quality. In the nucleation layer and coarsening layer stage, it tends to be a 3D growth mode, reducing the V / III ratio and increasing the pressure, which is conducive to the growth of crystal nuclei and grains, reducing the density of crystal nuclei, and reducing the dislocation density at the healing site.

[0024] S04: depositing a recovery layer on the novel roughening layer: the total thickness is 1500-2100 nm, which is a non-doped GaN layer, and the growth atmosphere is the same as the Al-doped roughening layer; the recovery layer structure comprises: Recovery layer 1, recovery layer 2, recovery layer 3; thickness: recovery layer 2 < recovery layer 1 < recovery layer 3; temperature: recovery layer 1 < recovery layer 2 < recovery layer 3; growth rate: recovery layer 1 < recovery layer 2 < recovery layer 3; Recovery layer 1: thickness 300~500nm, temperature 1030~1060℃, growth rate 4.5~6μm / h; Recovery layer 2: thickness 100~300nm, temperature 1070~1085℃, growth rate 6~7.5μm / h; Recovery layer 3: thickness is 1000-1300nm, temperature is around 1090~1100℃, growth rate is 8~9μm / h; In the recovery layer growth stage, the growth mode tends to be a 2D / 3D mixed growth mode. Increasing the temperature, increasing the V / III ratio, and reducing the pressure are beneficial to the healing of the grains, making the lateral growth rate greater than the vertical growth rate.

[0025] S05: depositing an unintentionally doped GaN layer on the recovery layer; S06: depositing a Si-doped N_GaN layer on the unintentionally doped GaN layer; S07: depositing an MQW layer on the N_GaN layer; S08: depositing an AL-doped P_GaN EBL layer on the MQW layer; S09: depositing a high Mg-doped P_GaN layer on the Al-doped P_GaN EBL layer.

[0026] like Figure 3 Shown is the use of Figure 1 Structure and Figure 2Comparison chart of LED epitaxial structure samples produced by the structure. It can be seen from the figure that the addition of Al can inhibit the growth of GaN on the non-C surface of the PSS substrate to a certain extent, reduce the starting dislocation and improve the lattice quality.

[0027] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A high-quality LED epitaxial structure, characterized in that: From bottom to top, it includes a substrate, a nucleation layer, a roughening layer, a recovery layer, an unintentional doping layer, an N-type GaN layer, a quantum well light-emitting layer, and a P-type GaN layer. The nucleation layer is a high-temperature pause layer / low-temperature buffer layer alternating cycle layer, and the roughening layer includes a high-pressure roughening layer and an Al-doped roughening layer in sequence.

2. A high-quality LED epitaxial structure as claimed in claim 1, characterized in that: The substrate is a sapphire substrate.

3. A high-quality LED epitaxial structure as claimed in claim 1, characterized in that: A P-type electron blocking layer is arranged between the quantum well light-emitting layer and the P-type GaN layer.

4. A high-quality LED epitaxial structure as claimed in claim 1, characterized in that: The low-temperature buffer layer is a non-doped GaN layer, and the high-temperature pause layer is a non-actual growth layer.

5. A high-quality LED epitaxial structure as claimed in claim 1, characterized in that: The high-pressure roughening layer is a non-actual production layer, and the Al-doped roughening layer is a low-pressure Al-doped GaN layer.

6. A high-quality LED epitaxial structure as claimed in claim 1, characterized in that: The recovery layer is a non-doped GaN layer.

7. A high-quality LED epitaxial structure as claimed in claim 1, characterized in that: The recovery layer includes recovery layer 1, recovery layer 2 and recovery layer 3, and the thickness is: recovery layer 2 < recovery layer 1 < recovery layer 3.

8. A method for preparing a high-quality LED epitaxial structure, characterized in that: The following steps are involved: S01: Provide a substrate; S02: Depositing a novel nucleation layer on a substrate: The novel nucleation layer structure comprises: a low temperature slow The punch layer is a non-doped GaN layer: the thickness of a single cycle growth is 20A~25A, the growth atmosphere is N2, set to 200~400sccm, and the low temperature is set at 800~850℃; the high temperature pause layer is a non-actual growth layer: the high temperature is set at 880~950℃; the growth atmosphere is N2 and H2: N2 is set to 200~400sccm, and H2 is set to 200~400sccm; the number of high and low temperature cycles is set to 5~15 times; S03: depositing a novel roughening layer on the novel nucleation layer: the novel roughening layer structure comprises: a high-pressure roughening layer: a non-actual production layer, a high pressure setting of 300-400 torr, a growth atmosphere of N2, H2, NH3: N2 setting of 150-300 sccm, H2 setting of 100-200 sccm, NH3 setting of 0-20 sccm; an AL-doped roughening layer: a low-pressure AL-doped GaN layer, a thickness of 300-500 nm, an AL amount of 5-20 slm, a low pressure setting of 150-250 torr, a growth atmosphere of N2, H2, NH3: N2 setting of 150-300 sccm, H2 setting of 100-200 sccm, NH3 setting of 150-300 sccm; S04: depositing a recovery layer on the novel roughening layer: the total thickness is 1500-2100 nm, which is a non-doped GaN layer, and the growth atmosphere is the same as the Al-doped roughening layer; the recovery layer structure comprises: Recovery layer 1, recovery layer 2, recovery layer 3; Thickness: recovery layer 2 < recovery layer 1 < recovery layer 3; Temperature: recovery layer 1 < recovery layer 2 < recovery layer 3; Growth rate: recovery layer 1 < recovery layer 2 < recovery layer 3; S05: depositing an unintentionally doped GaN layer on the recovery layer; S06: depositing a Si-doped N_GaN layer on the unintentionally doped GaN layer; S07: depositing an MQW layer on the N_GaN layer; S08: depositing an AL-doped P_GaN EBL layer on the MQW layer; S09: depositing a high Mg-doped P_GaN layer on the Al-doped P_GaN EBL layer.

9. A method for preparing a high-quality LED epitaxial structure according to claim 1, characterized in that: In the step S04, the recovery layer 1 has a thickness of 300-500 nm, a temperature of 1030-1060° C., and a growth rate of 4.5-6 μm / h; the recovery layer 2 has a thickness of 100-300 nm, a temperature of 1070-1085° C., and a growth rate of 6-7.5 μm / h; the recovery layer 3 has a thickness of 1000-1300 nm, a temperature of 1090-1100° C., and a growth rate of 8-9 μm / h.

Citation Information

Patent Citations

  • Light emitting diode epitaxial wafer and preparation method thereof

    CN104465918A

  • GaN-based light-emitting diode epitaxial wafer, preparation method of GaN-based light-emitting diode epitaxial wafer, and light-emitting diode

    CN109920722A

  • LED epitaxial bottom layer structure and growth method thereof

    CN111725371A

  • Preparation method of low-background-concentration gallium nitride epitaxial structure and epitaxial structure thereof

    CN115142126A

  • AlN buffer layer, LED wafer epitaxial wafer and preparation method thereof

    CN118630110A